Thromboembolism and anticoagulation after fontan surgery - Sangeetha Viswanathan (Wolters Kluwer Medknow Publications, 2016)
This review attempts to answer the common questions faced by a clinician regarding thromboembolism and thromboprophylaxis in patients following Fontan surgery. The review is in an easy to understand question and answer format and discusses the currently available literature on the subject in an attempt to arrive at practical clinically relevant solutions. Patients who have undergone the Fontan operation are at a high risk for thromboembolism. Based on available evidence, there is a strong rationale for thromboprophylaxis. However, it is not clear as to which agent should be administered to prevent thromboembolic events. While the available evidence suggests that antiplatelet agents alone may be as good as oral anticoagulants, there is a need for a large multicenter randomized control trial comparing these two common strategies to deliver a clear verdict.